CHEMICAL COMPOSITIONS AND BIOACTIVE COMPOUNDS OF LEMONGRASS ESSENTIAL OILS AGAINST MICROBIAL PATHOGEN AND DRUG-RESISTANT EXTENDED SPECTRUM ß-LACTAMASE (ESBL) PRODUCING GRAM-NEGATIVE - Watcharakul, Sirimaporn; Anomunee, Ruethaithip; Indoung, Saowakon (Life Sciences and Environment Journal, 2024)
The purpose of this study was to investigate and analyze the chemical compositions and major components of essential oils extracted from lemongrass leaves in the Sathing Phra Peninsula, Songkhla Province. Lemongrass was extracted by steam distillation, and its chemical composition was analyzed using Gas Chromatography Mass Spectrometry (GC-MS). It was discovered that the extracted essential oil contained up to 260 different chemical components, with important substances unique to the chemistry of lemongrass essential oil found in the monoterpene group, both terpene aldehyde and terpene alcohol in the form of citral, neral, geranial, geraniol, and others. In addition, there was a study of the effectiveness of lemongrass essential oil against six strains of pathogenic bacteria and drug-resistant bacteria, such as Escherichia coli ATCC 25923, Staphylococcus aureus SP1, Streptococcus pyogenes SV1, Escherichia coli A3 (ESBLs), Pseudomonas aeruginosa A2 (ESBLs), Klebsiella pneumoniae A1 (ESBLs). The disc diffusion assay method discovered that the extracted lemongrass essential oil had antimicrobial properties, with the most effective strain being S. pyogenes, which had an zone of inhibition size of 34.55±0.25 millimeters and could against all three strains of drug-resistant pathogens, with the highest efficiency against E. coli A3 (ESBLs), which had an inhibition zone size of 11.38±0.99 millimeters and inhibition zone size of Inhibits resemble to K. pneumoniae A1 (ESBLs), which has a size of 9.99±0.25 millimeters.